Palaeogeographic controls on climate and proxy interpretation - D. J. Lunt; A. Farnsworth; C. Loptson; G. L. Foster; P. Markwick; C. L. O'Brien; R. D. Pancost; S. A. Robinson; N. Wrobel (Climate of the Past, 2016)
During the period from approximately 150 to 35 million years ago, the Cretaceous–Paleocene–Eocene (CPE), the Earth was in a “greenhouse” state with little or no ice at either pole. It was also a period of considerable global change, from the warmest periods of the mid-Cretaceous, to the threshold of icehouse conditions at the end of the Eocene. However, the relative contribution of palaeogeographic change, solar change, and carbon cycle change to these climatic variations is unknown. Here, making use of recent advances in computing power, and a set of unique palaeogeographic maps, we carry out an ensemble of 19 General Circulation Model simulations covering this period, one simulation per stratigraphic stage. By maintaining atmospheric CO2 concentration constant across the simulations, we are able to identify the contribution from palaeogeographic and solar forcing to global change across the CPE, and explore the underlying mechanisms. We find that global mean surface temperature is remarkably constant across the simulations, resulting from a cancellation of opposing trends from solar and palaeogeographic change. However, there are significant modelled variations on a regional scale. The stratigraphic stage–stage transitions which exhibit greatest climatic change are associated with transitions in the mode of ocean circulation, themselves often associated with changes in ocean gateways, and amplified by feedbacks related to emissivity and planetary albedo. We also find some control on global mean temperature from continental area and global mean orography. Our results have important implications for the interpretation of single-site palaeo proxy records. In particular, our results allow the non-CO2 (i.e. palaeogeographic and solar constant) components of proxy records to be removed, leaving a more global component associated with carbon cycle change. This “adjustment factor” is used to adjust sea surface temperatures, as the deep ocean is not fully equilibrated in the model. The adjustment factor is illustrated for seven key sites in the CPE, and applied to proxy data from Falkland Plateau, and we provide data so that similar adjustments can be made to any site and for any time period within the CPE. Ultimately, this will enable isolation of the CO2-forced climate signal to be extracted from multiple proxy records from around the globe, allowing an evaluation of the regional signals and extent of polar amplification in response to CO2 changes during the CPE. Finally, regions where the adjustment factor is constant throughout the CPE could indicate places where future proxies could be targeted in order to reconstruct the purest CO2-induced temperature change, where the complicating contributions of other processes are minimised. Therefore, combined with other considerations, this work could provide useful information for supporting targets for drilling localities and outcrop studies.